ДО ПРОБЛЕМИ ПІЗНАВАЛЬНОЇ ДІЯЛЬНОСТІ ДИТИНИ-ДОШКІЛЬНИКА (Педагогіка вищої та середньої школи, 2022)
In the article the problem of the development of preschoolage children's cognitive activity is discussed. It suggests ways of development of their speech activity, which is variety of cognitive activity.